Conversational speech of school-age children after syllable-timed speech treatment for stuttering. (2nd January 2022) - Brown, Lisa; Wilson, Linda; Packman, Ann; Halaki, Mark; Andrews, Cheryl; O'Brian, Sue; Onslow, Mark; Menzies, Ross G.
Abstract: Purpose: The purpose of this laboratory study was to investigate whether rhythmic speech was primarily responsible for stuttering reductions in four school-aged children after the instatement stage of the Westmead Program of syllable-timed speech (STS) intervention. The study was designed to inform further development of the program. Reduction in variability of vowel duration is a marker of STS, and it was predicted that this would be present in the children's conversational speech after Stage 1 of the program if they were using STS. To strengthen such a finding, it was also predicted that there would be no reduction in articulation rate, sentence complexity, and utterance length after treatment, as there is evidence that reductions in these can reduce stuttering. Perceptual judgments of speech quality after treatment were also made by independent listeners. Method: Participants were four children, ages 8–11 years, who completed Stage 1 of an STS program and whose stuttering had reduced significantly. Pre-treatment (PRE) and post-treatment (POST) within-clinic audio-visual recordings of conversational speech were analysed for percentage of syllables stuttered, variability of vowel duration, articulation rate, and length and complexity of utterance. Four blinded listeners made perceptual judgments of speech quality in the POST recordings. Result: Recordings of all children showed that variability of vowel duration clearly reduced from the PRE to POST speech samples. Importantly, articulation rate and language use were not compromised. Some possible indicators of rhythmicity were identified in one child in the perceptual study. Conclusion: The findings suggest that STS was primarily responsible for the clinically significant reductions in stuttering after Stage 1 of the program. There is an urgent need for more evidence-based interventions for stuttering in this age group and further development of STS interventions is warranted.